Peel Ultrastructure During Developmental Stages of Citrus Sinensis (L.) Osbeck. - Indira Prabasari (Universitas Muhammadiyah Yogyakarta, 2014)
The peel structureof Valencia orange (Citrus sinensis (L.) Osbeck) was examined using Scanning Electron Microscopy (SEM) and showed the distinct regions of the peel: the outer-yellowish part that was called the flavedo and the inner part of the peel that was called the albedo. The flavedo has compact cells with oil glands embedded in it whereas the albedo contains of spongy cells with vascular bundles embedded in it. The ultrastructural examination of the albedo during development revealed the changes of albedo morphology from compact tissue to the loosely arranged tissue. In addition, the distribution of polysaccharide cell walls was observed with histochemical staining and later the distribution of peptic polysaccharide was conducted using anti-pectin monoclonal antibodies (mAbs). Histochemical staining during development demonstrated the difference of abundance of polysaccharide at the tissue level. Furthermore, the distribution of homogalacturonan (HG) was studied with mAb JIM5 that recognizes low methyl-esterified HG and JJM7 which labels high methyl-esterified HG. The observation at the fruit level was conducted using tissue printing and the result showed that low and high methyl-esterified HG was distributed almost similar at the fruit level. Further experiment at the tissue level was performed using Light Microscopy (LM) and revealed that HG was found more abundant in the albedo and vascular bundle followed by the flavedo and oil gland.